Persistent scarring and dilated cardiomyopathy suggest incomplete regeneration of the apex resected neonatal mouse myocardium — A 180 days follow up study. (January 2016) - Andersen, Ditte Caroline; Jensen, Charlotte Harken; Baun, Christina; Hvidsten, Svend; Zebrowski, David C.; Engel, Felix Benedikt; Sheikh, Søren Paludan
Abstract: Heart damage in mammals is generally considered to result in scar formation, whereas zebrafish completely regenerate their hearts following an intermediate and reversible state of fibrosis after apex resection (AR). Recently, using the AR procedure, one-day-old mice were suggested to have full capacity for cardiac regeneration as well. In contrast, using the same mouse model others have shown that the regeneration process is incomplete and that scarring still remains 21 days after AR. The present study tested the hypothesis that like in zebrafish, fibrosis in neonatal mammals could be an intermediate response before the onset of complete heart regeneration. Myocardial damage was performed by AR in postnatal day 1 C57BL/6 mice, and myocardial function and scarring assessed at day 180 using F-18-fluorodeoxyglucose positron emission tomography (FDG-PET) and histology, respectively. AR mice exhibited decreased ejection fraction and wall motion with increased end-diastolic and systolic volumes compared to sham-operated mice. Scarring with collagen accumulation was still substantial, with increased heart size, while cardiomyocyte size was unaffected. In conclusion, these data thus show that apex resection in mice results in irreversible fibrosis and dilated cardiomyopathy suggesting that cardiac regeneration is limited in neonatal mammals and thus distinct from the regenerative capacity seen in zebrafish. Highlights: Zebrafish hearts regenerate following apex resection (AR) through a stage of fibrosis. We hypothesised that the day 21, fibrosis reported in mouse AR hearts is transient as well. Yet, the lesioned apex displays reduced wall motion and substantial scarring at day 180. Dilated cardiomyopathy as evaluated by positron emission tomography was seen at day 180 in AR hearts. In conclusion, fibrosis is persistent in mouse hearts following AR.